Single‐Site AuI Catalyst for Silane Oxidation with Water. Issue 5 (11th December 2017) - Chen, Zheng; Zhang, Qi; Chen, Wenxing; Dong, Juncai; Yao, Hurong; Zhang, Xiangbo; Tong, Xuanjue; Wang, Dingsheng; Peng, Qing; Chen, Chen; He, Wei; Li, Yadong
Abstract: Single‐site Au anchored on mpg‐C3 N4 (519 ppm Au loading) is developed as a highly active, selective, and stable catalyst for the oxidation of silanes with water with a turnover frequency as high as 50 200 h −1, far exceeding most known catalysts based on total gold content. Other hydrosilanes bearing unsaturated functional groups also lead to corresponding silanols under mild reaction conditions without formation of any side products in good or excellent yields. The spherical aberration correction electron microscopy and extended X‐ray absorption fine structure measurements both confirm the atomic dispersion of Au atoms stabilized by mpg‐C3 N4 . The coordination of the catalytically active Au I by three nitrogen or carbon atoms in the tri‐s‐triazine repeating units not only prevents the Au atoms from aggregation, but also renders the surface Au I highly active, which is completely different than homogeneous Au I species. Abstract : Au anchored on mpg‐C3 N4 (519 ppm Au loading) is developed as a highly active, selective, and stable catalyst for the oxidation of silanes with water, with a turnover frequency as high as 50 200 h −1, which far exceeds that of most catalysts, based on total gold content.